2014
DOI: 10.1007/s12010-014-1236-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium, Magnesium, and Iron Ions on Aerobic Granulation

Abstract: In this study, we investigated the effect of different multivalent cations on granule formation. Previous experiments showed that formation of matrix EPS and their structure depend of the presence of divalent cations. This study indicates that trivalent cations are also playing an important role. However, the more compact granules were formed in the presence of all cations. The authors tried also to determine changes in proteomic profile of slime and tightly bound EPS. These results showed that matrix EPS is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Gao et al ( 2011b ) found that higher organic loading rate with added Ca 2+ gave larger granules with higher polysaccharide-to-protein ratio. Kończak et al ( 2014 ) compared the binding of divalent cations (Ca 2+ and Mg 2+ ) and multivalent cations (Fe 3+ ) to EPS in aerobic granules. It was found that granules fed with Ca 2+ and Mg 2+ contained more polysaccharide than the Fe 3+ -fed reactor, whereas the protein content was higher in all reactors fed with cations compared to the control without.…”
Section: Process Configurations and Operational Conditions Affecting mentioning
confidence: 99%
“…Gao et al ( 2011b ) found that higher organic loading rate with added Ca 2+ gave larger granules with higher polysaccharide-to-protein ratio. Kończak et al ( 2014 ) compared the binding of divalent cations (Ca 2+ and Mg 2+ ) and multivalent cations (Fe 3+ ) to EPS in aerobic granules. It was found that granules fed with Ca 2+ and Mg 2+ contained more polysaccharide than the Fe 3+ -fed reactor, whereas the protein content was higher in all reactors fed with cations compared to the control without.…”
Section: Process Configurations and Operational Conditions Affecting mentioning
confidence: 99%
“…40 Similarly, Fe 3+ is also linked to EPS binding as well as in bio-coagulation allowing other organic and inorganic molecules to aggregate giving granules a compact structure and increased settleability. 41 It is noted that although Ca 2+ was not added in the synthetic wastewater, but approximately 40 mg L −1 of Ca 2+ was present in the local tap water used to prepare the synthetic feed. In addition, precipitates of P were also detected on granular surface as shown in Fig.…”
Section: Characterization Of Aerobic Granules During Continuous Flow mentioning
confidence: 99%
“…Reduction in settling time is expected to impose a selective pressure towards retention and proliferation of microorganisms in sludge that can settle faster, while Ca 2+ and Mg 2+ are expected to promote aggregation (Li et al 2009;Kończak et al 2014). A VER of 77 % was maintained and C/N ratio was reduced to 4:1 to ensure better COD removal from the treated effluent and to make the process more economical.…”
Section: Granulation Of Sludgementioning
confidence: 99%
“…Various researchers have also reported a beneficial role of divalent and trivalent cations (Ca 2+ , Mg 2+ , and Fe 3+ ) in aerobic granulation. Binding of these cations to negatively charged groups present on bacterial surfaces and extracellular polysaccharides is reported to facilitate cell-to-cell adhesion (van Loosdrecht et al 1987;Bruus et al 1992;Kończak et al 2014). Divalent cations have also been linked with higher production of polysaccharides which in turn affects the structural integrity of microbial aggregates and aerobic granules (Shen et al 1993;Sutherland 2001).…”
Section: Introductionmentioning
confidence: 99%